Release film for electronic equipment and production method thereof

By adding conductive polythiophene to the polyethylene terephthalate film substrate to the polyethylene terephthalate film substrate antistatic filler coated with nanoantimide doped tin oxide and high-temperature filler with high-temperature benzimidazole ring, the shortcomings of the antistatic and high-temperature resistance of the polyethylene terephthalate film substrate are solved, and better protection effect of electronic equipment is achieved.

CN119875181APending Publication Date: 2025-04-25FOSHAN JIASIDA THIN FILM TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510031226.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Polyethylene terephthalate as a release film substrate has insufficient antistatic properties and high temperature resistance, which may cause damage to electronic components during the manufacturing process of electronic equipment.

Method used

A release film consisting of a film substrate and an aqueous non-silicon release agent is used. Antistatic filler and high-temperature filler are added to the film substrate. The antistatic filler is composed of conductive polythiophene coated with nanoantimmony doped tin oxide. The high-temperature filler has rigid high-temperature benzimidazole rings.

Benefits of technology

The anti-static and high-temperature resistance of the release film is improved, so that it can more effectively protect electronic components during the manufacturing process of electronic equipment and avoid static damage and high-temperature damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875181A_ABST
    Figure CN119875181A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of anti-static film materials, and discloses a release film for electronic equipment and a production method of the release film. The release film is composed of a film base material and a water-based non-silicon release agent coated on the surface of the film base material; the film base material comprises the following raw materials: polyethylene glycol terephthalate resin, an antistatic filler, a high-temperature-resistant filler, an antioxidant and a lubricant; by adding the antistatic filler, a stable conductive network is formed in a matrix, surface charge accumulation is reduced, and the film substrate is endowed with excellent antistatic performance; by adding the high-temperature-resistant filler, the high-temperature resistance and toughness of the film base material are enhanced, the film base material can keep stable performance and continuously play a role in a high-temperature environment, static electricity is effectively isolated, electronic equipment is protected, and the film base material has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antistatic film materials, and in particular to a release film for electronic equipment and a production method thereof. Background Art

[0002] With the development of science and technology, electronic equipment has become an indispensable part of modern society. Electronic equipment products are constantly innovating and developing, and the role of release film in electronic equipment manufacturing has gradually become prominent. Release film can also be called isolation film, peeling film, separation film, adhesive barrier film, protective film, etc. It is a thin film with separation properties on the surface. The main function of release film in electronic equipment is to protect electronic components from pollution, damage and scratches during manufacturing and assembly, protect electronic components that do not need to be bonded, prevent glue from penetrating into the circuit area, and perform electronic packaging demolding and flexible circuit board lamination. Release film generally coats a release agent on the film substrate to achieve the release function. Common materials used to prepare release film substrates include polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polyurethane (PU), etc. Polyethylene terephthalate has excellent mechanical properties, chemical stability, electrical properties, high transparency and recyclability, and has become the preferred material for release film base film; considering that the silicon element contained in the silicone release agent may cause poor processing and defects in the manufacturing process of some special electronic equipment, non-silicone release agents are selected.

[0003] The release film used in electronic equipment needs to have antistatic and high temperature resistance properties. The antistatic property prevents the static electricity generated by electromagnetic waves and friction from damaging the electronic components in the electronic equipment. At the same time, the release film often comes into direct contact with electronic components during use, and the electronic components generate high temperatures. If the release film substrate does not have high temperature resistance, the release film cannot be used normally. By improving the release film substrate, the prepared release film has excellent antistatic and high temperature resistance properties to ensure the protective effect of the release film on the electronic equipment.

[0004] The patent with publication number CN117024806B discloses a method for preparing a high-temperature resistant enhanced PET release film. By adding cerium-barium co-modified zirconium oxide particles, the synergistic effect of cerium and barium can promote the zirconium oxide particles to form stable clusters or particles, prevent the growth of zirconium oxide grains and the diffusion of grain boundaries, enhance the thermal stability and oxidation resistance of the material, increase the tensile strength and hardness of the material, and thus improve the durability and mechanical properties. However, the patent only considers the high-temperature resistance of the release film, and does not consider that in actual applications, when the PET release film is used in electronic equipment, it does not have antistatic properties, which causes damage to electronic components. Therefore, the present invention provides a release film that can be directly used in electronic equipment, has excellent antistatic properties and high-temperature resistance, and has broad application prospects. Summary of the invention

[0005] The purpose of the present invention is to provide a release film for electronic equipment and a production method thereof, which solves the following technical problems:

[0006] (1) The problem of poor antistatic performance of polyethylene terephthalate as a release film substrate is solved;

[0007] (2) The problem of poor high temperature resistance of polyethylene terephthalate as a release film substrate is solved.

[0008] The purpose of the present invention can be achieved through the following technical solutions:

[0009] A release film for electronic equipment, the release film consists of a film substrate and an aqueous non-silicon release agent coated on the surface of the film substrate; the film substrate comprises the following raw materials in parts by weight: 85-100 parts of polyethylene terephthalate resin, 4-8 parts of antistatic filler, 5-8 parts of high temperature resistant filler, 1-3 parts of antioxidant, and 1-3 parts of lubricant.

[0010] Furthermore, the preparation method of the antistatic filler is as follows:

[0011] Add nano antimony-doped tin oxide to chloroform solution, ultrasonically disperse for 0.5-1h, add thiophene monomer, stir for 1-3h, add anhydrous ferric chloride after the thiophene monomer is adsorbed on the surface of nano antimony-doped tin oxide, stir for 10-12h at 15-25°C, evaporate the solvent, add hydrochloric acid solution, stir for 1-2h, filter, repeat the process 2-4 times until the filtrate is colorless, wash, and dry at 45-55°C for 8-10h to obtain an antistatic filler.

[0012] By adopting the above technical scheme, nano antimony-doped tin oxide can interact with the sulfur atoms in the thiophene monomer to form a chemical bond. The oxidizing effect of anhydrous ferric chloride is used to make the thiophene monomer in situ oxidatively polymerize on the surface of the nano antimony-doped tin oxide to form a structure of polythiophene-coated nano antimony-doped tin oxide to obtain an antistatic filler.

[0013] Furthermore, the mass ratio of the nano antimony-doped tin oxide to the thiophene monomer is 1:0.1-0.3.

[0014] Furthermore, the concentration of the hydrochloric acid solution is 1-1.5 mol / L.

[0015] Furthermore, the preparation method of the high temperature resistant filler is as follows:

[0016] Add epoxidized natural rubber to N,N-dimethylformamide, stir evenly, add 1H-benzimidazole-2-carboxylic acid and a catalyst, heat to 100-120°C, react for 4-8h, precipitate, wash, and vacuum dry to obtain a high temperature resistant filler.

[0017] By adopting the above technical scheme, the active epoxy groups in the epoxidized natural rubber can undergo a ring-opening reaction with the active carboxyl groups in the 1H-benzimidazole-2-carboxylic acid structure to obtain a high-temperature resistant filler grafted with a high-temperature resistant rigid ring and a hydroxyl group.

[0018] Furthermore, the epoxidation degree of the epoxidized natural rubber is 30-40%.

[0019] Furthermore, the catalyst is tetrabutylammonium bromide or tetramethylammonium chloride.

[0020] Furthermore, the water-based non-silicone release agent has a model of 228-21CN; the antioxidant is pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid) ester and tris(2,4-di-tert-butylphenyl) phosphite; and the lubricant is any one of zinc stearate, N,N-ethylene bis(stearic acid amide) or calcium stearate.

[0021] A method for producing a release film for electronic equipment comprises the following steps:

[0022] Step 1, adding polyethylene terephthalate resin, antistatic filler, high temperature resistant filler, antioxidant and lubricant into a mixer, and mixing them evenly to obtain a mixture;

[0023] Step 2: Add the mixed material into a twin-screw extruder, melt-extrude, and then longitudinally stretch it at 100-180° C. using a biaxial stretching device with a longitudinal stretching ratio of 2.5-4.5 times to obtain a stretched sheet;

[0024] Step 3, the stretched sheet is transversely stretched at 100-200° C., the transverse stretching ratio is 2.5-4.5 times, and the film is fixed at 200-250° C. After cooling, the polyethylene terephthalate release film substrate can be obtained;

[0025] Step 4: corona treat the polyethylene terephthalate release film substrate and apply a water-based non-silicone release agent with a dry coating weight of 0.1-0.5 g / m 2 , after drying and curing at 100-120℃ for 1-3min, a release film is obtained.

[0026] Furthermore, in step three, the polyethylene terephthalate release film substrate has a thickness of 25-50 μm.

[0027] Beneficial effects of the present invention:

[0028] (1) The antistatic filler prepared by the present invention is composed of conductive polythiophene-coated nano antimony-doped tin oxide, which can form a stable conductive network in a polyethylene terephthalate matrix, reduce surface charge accumulation, and jointly improve the antistatic performance of the matrix. The nano antimony-doped tin oxide is coated with polythiophene, which improves the compatibility with the matrix, and can more effectively exert the advantages of the conductivity of the nano antimony-doped tin oxide and enhance the mechanical properties of the matrix. Polythiophene plays a bridging role between the nano antimony-doped tin oxide and the matrix, fixes the nano antimony-doped tin oxide inside the matrix, and can play a role for a long time, avoiding the uneven dispersion of the nano antimony-doped tin oxide affecting the formation of the conductive network, thereby reducing the antistatic performance. Therefore, the antistatic filler gives the film substrate excellent antistatic performance and can play a role for a long time.

[0029] (2) The high temperature resistant filler prepared by the present invention has a rigid high temperature resistant benzimidazole ring. After being added to the matrix polyethylene terephthalate, the high temperature resistance of the matrix is ​​improved. The high temperature resistant filler contains active hydroxyl groups that can react with the active carboxyl groups in the polyethylene terephthalate structure to produce crosslinking, thereby further improving the high temperature resistance of the membrane substrate. At the same time, the epoxidized natural rubber can form stress dispersion points in the matrix. When impacted by external force, the stress dispersion points can disperse and absorb the impact energy to avoid stress concentration that causes the membrane substrate to be damaged. It can effectively enhance the toughness of the membrane substrate, so that the membrane substrate can maintain stable performance even in a high temperature environment.

[0030] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0032] Figure 1 The infrared spectrum of the high temperature resistant filler prepared in the example. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] Preparation of antistatic fillers

[0036] 1 g of nano antimony-doped tin oxide (model ZH-ATO50N, purchased from Hefei AVIC Nano-Technology Development Co., Ltd.) was added to a chloroform solution and ultrasonically dispersed for 1 h. 0.1 g of thiophene monomer was added and stirred for 2 h. After the thiophene monomer was adsorbed onto the surface of the nano antimony-doped tin oxide, 0.4 g of anhydrous ferric chloride was added and stirred at 20 ° C for 10 h. The solvent was evaporated, 1 mol / L of hydrochloric acid solution was added, stirred for 1 h, filtered, and the process was repeated 3 times until the filtrate was colorless. The solution was washed and dried at 50 ° C for 8 h to obtain an antistatic filler.

[0037] The sulfur element analysis of nano antimony doped tin oxide and antistatic filler was carried out using a Var io MACRO element analyzer. According to the results, the nano antimony doped tin oxide does not contain sulfur element, and the sulfur content in the antistatic filler is 2.03%. Therefore, the sulfur element in the antistatic filler comes from polythiophene.

[0038] 2. Preparation of high temperature resistant filler

[0039] 2.5 g of epoxidized natural rubber with an epoxidation degree of 40% was added to N,N-dimethylformamide, and after stirring evenly, 0.5 g of 1H-benzimidazole-2-carboxylic acid and 0.1 g of tetrabutylammonium bromide were added, the temperature was raised to 110°C, the reaction was carried out for 6 hours, precipitation was carried out, washing was carried out, and vacuum drying was carried out to obtain a high temperature resistant filler.

[0040] Using Fourier infrared spectrometer, the high temperature resistant filler and potassium bromide were ground and sliced, and infrared test was performed. The test results are shown in Figure 1 ,Depend on Figure 1 It can be seen that in the infrared spectrum of high temperature resistant fillers, 3438cm -1 The characteristic absorption peak of -OH appears at 3387cm -1 The characteristic absorption peak of the imidazole ring NH appears at 1732 cm -1 The characteristic absorption peak of C=O in the ester group appears at 1553 cm -1 The characteristic absorption peak of imidazole ring C=N appears at 1263cm -1 The characteristic absorption peak of epoxy group appears at

[0041] 3. Preparation of polyethylene terephthalate release film substrate

[0042] Step 1, adding 85g of polyethylene terephthalate resin, 4g of antistatic filler, 5g of high temperature resistant filler, 0.5g of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid), 0.5g of tris(2,4-di-tert-butylphenyl)phosphite and 1g of calcium stearate into a mixer, and mixing well to obtain a mixture;

[0043] Step 2: Add the mixed material into a twin-screw extruder, melt-extrude, and then longitudinally stretch it at 100° C. using a biaxial stretching device with a longitudinal stretching ratio of 2.5 times to obtain a stretched sheet;

[0044] Step 3: Transversely stretch the stretched sheet at 100° C. with a transverse stretching ratio of 2.5 times, and fix it at 200° C. After cooling, a polyethylene terephthalate release film substrate with a thickness of 25 μm can be obtained.

[0045] Example 2

[0046] Preparation of polyethylene terephthalate release film substrate

[0047] Step 1, adding 90g of polyethylene terephthalate resin, 6g of the antistatic filler prepared in Example 1, 6g of the high temperature resistant filler prepared in Example 1, 1g of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid), 1g of tris(2,4-di-tert-butylphenyl)phosphite and 2g of calcium stearate into a mixer, and mixing well to obtain a mixture;

[0048] Step 2: Add the mixed material into a twin-screw extruder, melt-extrude, and then longitudinally stretch it at 140° C. using a biaxial stretching device with a longitudinal stretching ratio of 3 times to obtain a stretched sheet;

[0049] Step 3: The stretched sheet is transversely stretched at 150° C. with a transverse stretching ratio of 3.5 times, and is shaped at 220° C. After cooling, a polyethylene terephthalate release film substrate with a thickness of 35 μm is obtained.

[0050] Example 3

[0051] Preparation of polyethylene terephthalate release film substrate

[0052] Step 1, 95g of polyethylene terephthalate resin, 7g of the antistatic filler prepared in Example 1, 7g of the high temperature resistant filler prepared in Example 1, 1.5g of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid), 1g of tris(2,4-di-tert-butylphenyl)phosphite and 2g of calcium stearate are added into a mixer, and mixed evenly to obtain a mixture;

[0053] Step 2: adding the mixed material into a twin-screw extruder, and after melt extrusion, longitudinally stretching the mixed material through a biaxial stretching device at 160° C. with a longitudinal stretching ratio of 3.5 times to obtain a stretched sheet;

[0054] Step 3: The stretched sheet is transversely stretched at 175° C. with a transverse stretching ratio of 4 times, and is shaped at 230° C. After cooling, a polyethylene terephthalate release film substrate with a thickness of 45 μm is obtained.

[0055] Example 4

[0056] Preparation of polyethylene terephthalate release film substrate

[0057] Step 1, 100g of polyethylene terephthalate resin, 8g of the antistatic filler prepared in Example 1, 8g of the high temperature resistant filler prepared in Example 1, 1.5g of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid), 1.5g of tris(2,4-di-tert-butylphenyl)phosphite and 3g of calcium stearate are added into a mixer, and mixed evenly to obtain a mixture;

[0058] Step 2: adding the mixed material into a twin-screw extruder, and after melt extrusion, longitudinally stretching the mixed material through a biaxial stretching device at 180° C. with a longitudinal stretching ratio of 4.5 times to obtain a stretched sheet;

[0059] Step 3: Transversely stretch the stretched sheet at 200° C. with a transverse stretching ratio of 4.5 times, and shape it at 250° C. After cooling, a polyethylene terephthalate release film substrate with a thickness of 50 μm can be obtained.

[0060] Comparative Example 1

[0061] Preparation of polyethylene terephthalate release film substrate

[0062] Step 1, adding 90g of polyethylene terephthalate resin, 6g of the antistatic filler prepared in Example 1, 1g of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid), 1g of tris(2,4-di-tert-butylphenyl)phosphite and 2g of calcium stearate into a mixer, and mixing them evenly to obtain a mixture;

[0063] Step 2: Add the mixed material into a twin-screw extruder, melt-extrude, and then longitudinally stretch it at 140° C. using a biaxial stretching device with a longitudinal stretching ratio of 3 times to obtain a stretched sheet;

[0064] Step 3: The stretched sheet is transversely stretched at 150° C. with a transverse stretching ratio of 3.5 times, and is shaped at 220° C. After cooling, a polyethylene terephthalate release film substrate with a thickness of 35 μm is obtained.

[0065] Comparative Example 2

[0066] Preparation of polyethylene terephthalate release film substrate

[0067] Step 1, adding 90g of polyethylene terephthalate resin, 6g of the high temperature resistant filler prepared in Example 1, 1g of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid), 1g of tris(2,4-di-tert-butylphenyl)phosphite and 2g of calcium stearate into a mixer, and mixing them evenly to obtain a mixture;

[0068] Step 2: Add the mixed material into a twin-screw extruder, melt-extrude, and then longitudinally stretch it at 140° C. using a biaxial stretching device with a longitudinal stretching ratio of 3 times to obtain a stretched sheet;

[0069] Step 3: The stretched sheet is transversely stretched at 150° C. with a transverse stretching ratio of 3.5 times, and is shaped at 220° C. After cooling, a polyethylene terephthalate release film substrate with a thickness of 35 μm is obtained.

[0070] Comparative Example 3

[0071] Preparation of polyethylene terephthalate release film substrate

[0072] Step 1, adding 90g of polyethylene terephthalate resin, 6g of nano antimony-doped tin oxide, 6g of the high temperature resistant filler prepared in Example 1, 1g of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid), 1g of tris(2,4-di-tert-butylphenyl)phosphite and 2g of calcium stearate into a mixer, and mixing well to obtain a mixture;

[0073] Step 2: Add the mixed material into a twin-screw extruder, melt-extrude, and then longitudinally stretch it at 140° C. using a biaxial stretching device with a longitudinal stretching ratio of 3 times to obtain a stretched sheet;

[0074] Step 3: The stretched sheet is transversely stretched at 150° C. with a transverse stretching ratio of 3.5 times, and is shaped at 220° C. After cooling, a polyethylene terephthalate release film substrate with a thickness of 35 μm is obtained.

[0075] Comparative Example 4

[0076] Preparation of polyethylene terephthalate release film substrate

[0077] Step 1, adding 90g of polyethylene terephthalate resin, 6g of the antistatic filler prepared in Example 1, 6g of epoxidized natural rubber, 1g of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid), 1g of tris(2,4-di-tert-butylphenyl)phosphite and 2g of calcium stearate into a mixer, and mixing well to obtain a mixture;

[0078] Step 2: Add the mixed material into a twin-screw extruder, melt-extrude, and then longitudinally stretch it at 140° C. using a biaxial stretching device with a longitudinal stretching ratio of 3 times to obtain a stretched sheet;

[0079] Step 3: The stretched sheet is transversely stretched at 150° C. with a transverse stretching ratio of 3.5 times, and is shaped at 220° C. After cooling, a polyethylene terephthalate release film substrate with a thickness of 35 μm is obtained.

[0080] Performance Testing

[0081] The polyethylene terephthalate release film substrates prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were tested:

[0082] The polyethylene terephthalate release film substrates prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were prepared into samples of the same size and thickness that met the test requirements. The tensile strength and elongation at break of the samples were tested in accordance with standard GB / T1040.3-2006 to determine the mechanical properties. The samples were placed in a 150°C constant temperature oven for aging for 24 hours, and the tensile strength after heat aging was tested to determine the high temperature resistance of the samples. The surface resistivity of the samples was tested using a ZC-90B high insulation resistance tester to determine the antistatic properties of the samples. The test results are shown in the following table:

[0083]

[0084] As can be seen from the above table, the polyethylene terephthalate release film substrates prepared in Examples 1 to 4 of the present invention have excellent mechanical properties, antistatic properties and high temperature resistance. Comparative Example 1 does not add high temperature resistant fillers, and cannot use epoxidized natural rubber and 1H-benzimidazole-2-carboxylic acid to graft, introduce high temperature resistant rigid rings, and cross-link with polyethylene terephthalate to further enhance high temperature resistance and toughness. Therefore, the tensile strength and elongation at break test results after aging are poor; Comparative Example 2 does not add antistatic fillers, and cannot use polythiophene-coated nano antimony-doped tin oxide to enhance the mechanical properties of tensile strength. , forming a conductive network, resulting in static electricity accumulation, so the tensile strength and surface resistivity test results are poor; Comparative Example 3 added nano antimony-doped tin oxide and high-temperature resistant fillers, and the nano antimony-doped tin oxide was directly added without modification, resulting in agglomeration problems, a decrease in tensile strength, and a stable conductive network could not be formed, so the tensile strength and surface resistivity test results were poor; Comparative Example 4 added epoxidized natural rubber and antistatic fillers, and was unable to utilize the high-temperature resistant rigid benzimidazole ring and cross-linking with polyethylene terephthalate to enhance the high-temperature resistance and toughness, so the tensile strength and elongation at break test results after aging were poor.

[0085] The polyethylene terephthalate release film substrate prepared in Example 1 to Example 4 is used to prepare a release film. The specific preparation method is as follows:

[0086] The polyethylene terephthalate release film substrate was corona treated and coated with a water-based non-silicone release agent 228-21CN with a dry coating weight of 0.3 g / m 2 , after drying and curing at 100°C for 2 minutes, a release film was obtained.

[0087] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A release film for electronic equipment, characterized in that: The release film is composed of a film substrate and a water-based non-silicon release agent coated on the surface of the film substrate; the film substrate includes the following raw materials in parts by weight: 85-100 parts of polyethylene terephthalate resin, 4-8 parts of antistatic filler, 5-8 parts of high temperature resistant filler, 1-3 parts of antioxidant, and 1-3 parts of lubricant.

2. A release film for electronic equipment according to claim 1, characterized in that: The preparation method of the antistatic filler is as follows: Add nano antimony-doped tin oxide to chloroform solution, ultrasonically disperse for 0.5-1h, add thiophene monomer, stir for 1-3h, add anhydrous ferric chloride after the thiophene monomer is adsorbed on the surface of nano antimony-doped tin oxide, stir for 10-12h at 15-25°C, evaporate the solvent, add hydrochloric acid solution, stir for 1-2h, filter, repeat the process 2-4 times until the filtrate is colorless, wash, and dry at 45-55°C for 8-10h to obtain an antistatic filler.

3. A release film for electronic equipment according to claim 2, characterized in that: The mass ratio of the nano antimony-doped tin oxide to the thiophene monomer is 1:0.1-0.

3.

4. A release film for electronic equipment according to claim 2, characterized in that: The concentration of the hydrochloric acid solution is 1-1.5 mol / L.

5. The release film for electronic equipment according to claim 1, characterized in that: The preparation method of the high temperature resistant filler is as follows: Add epoxidized natural rubber to N, N-dimethylformamide, stir evenly, add 1H-benzimidazole-2-carboxylic acid and a catalyst, heat to 100-120°C, react for 4-8h, precipitate, wash, and vacuum dry to obtain a high temperature resistant filler.

6. A release film for electronic equipment according to claim 5, characterized in that: The epoxidation degree of the epoxidized natural rubber is 30-40%.

7. The release film for electronic equipment according to claim 5, characterized in that: The catalyst is tetrabutylammonium bromide or tetramethylammonium chloride.

8. The release film for electronic equipment according to claim 1, characterized in that: The water-based non-silicone release agent has a model number of 228-21CN; the antioxidant is pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid) and tris(2,4-di-tert-butylphenyl)phosphite; and the lubricant is any one of zinc stearate, N,N-ethylene bisstearic acid amide or calcium stearate.

9. A method for producing a release film for electronic equipment according to claim 1, characterized in that: The following steps are involved: Step 1, adding polyethylene terephthalate resin, antistatic filler, high temperature resistant filler, antioxidant and lubricant into a mixer, and mixing them evenly to obtain a mixture; Step 2: Add the mixed material into a twin-screw extruder, melt-extrude, and then longitudinally stretch it at 100-180° C. using a biaxial stretching device with a longitudinal stretching ratio of 2.5-4.5 times to obtain a stretched sheet; Step 3, the stretched sheet is transversely stretched at 100-200° C., the transverse stretching ratio is 2.5-4.5 times, and the film is fixed at 200-250° C. After cooling, the polyethylene terephthalate release film substrate can be obtained; Step 4: corona treat the polyethylene terephthalate release film substrate and apply a water-based non-silicone release agent with a dry coating weight of 0.1-0.5 g / m 2 After drying and curing at 100-120°C for 1-3 minutes, a release film is obtained.

10. The method for producing a release film for electronic equipment according to claim 9, characterized in that: In step 3, the thickness of the polyethylene terephthalate release film substrate is 25-50 μm.

Citation Information

Patent Citations

  • A method for preparing high temperature resistant enhanced PET release film

    CN117024806B